Various Ethno Medicinal Plants used in the Preparation of Apong, a Traditional Beverage use by Mising Tribe of upper Assam - Barnali Gogoi,Mayurakhi Dutta,Prodyut Mondal (Journal of Applied Pharmaceutical Science, 2013)
The main objective of this article is to document and represent the medicinal herb used for the preparation of Apong by the Mising tribal community. North-East India is inhabited by many indigenous tribes and as a part of their socio-cultural life, most of these tribes prepare their own household liquors, mostly using rice grains as the substrate. Each of the tribes also prepares their own unique starter cultures to carry out fermentation, and each type is a mixture of different parts of various plant species. There are 39 plants documented here which possess distinct medicinal values. The paper reflects the rich ethno medicinal values of the herbs. The informations are collected by the active field survey in three villages of Sibsagar district in Assam, and through the available local literature. This review will help to researchers and scholars to investigate the proper bio-molecules and its’ accessible pharmacological responses. The further scrutiny and evaluation of the safety parameters of each component of the herb used in Apong may be investigate to develop a pharmacologically potent lead molecule.
Keywords: Apong, Mising